Perancangan Sistem Informasi Akuntansi Laporan Keuangan Standar PSAK 45s - Lita Lara Rosita (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
The time of managing financial reporting is still done by making the calculation in the MS. Excel, so that the accounting records in the Treasurer is less effective at generating financial reports quickly and accurately. As well as financial statements have not been fully made use of accounting standards in force in Indonesia. To these problems, the writer took the title "Designing Standard Financial Statements of Accounting Information Systems PSAK 45s". Research design that writer used is research design with the data of primary / secondary analytical and descriptive, this type of research that writer used is academic research, type of data that the authors use quantitative and qualitative data, the authors use the research method is descriptive research methods and survey methods, data collection techniques that I use is a field study consisting of interviews and observations and literature studies, method development system that I use is a process-oriented methodology, data, and output, the structure of system development which writer use is Waterfall. The author’s purpose to make the design of accounting information system of financial reporting standards of PSAK 45, the expected data processing cash receipts and disbursements in the Pemberdayaan dan Kesejahteraan Keluarga city Cimahi well be computerized so that no human error and the resulting output financial statements will be accurate and relevan.